Relationship between the Number of CD4+ and CD8+ Cells in Patients with COVID-19 (Coronavirus Disease 2019) at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Hidayatullah; Zen Ahmad; Phey Liana; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The pathogenesis of COVID-19 involves complex immunological processes that can predispose to disease severity. In COVID-19 patients, there will be changes in the number of CD4 + and CD8 + cells which are part of lymphocyte cells in the specific immune system. This study aims to see the relationship between CD4+ and CD8+ cell counts in COVID- 19 patients at Dr. Mohammad Hoesin Hospital Palembang, Indonesia. Methods: This research is an observational study with a case series approach. A total of 30 study subjects who were COVID-19 patients participated in this study. The number of CD4+ and CD8+ cells was assessed, then correlation analysis was performed with the Spearman test, p<0.05. Results: The correlation between CD4+ and CD8+ has a value of R = 0.875 and p<0.01. This shows that CD4+ and CD8+ have a strong positive correlation and are statistically significant. Conclusion: The increase in the number of CD4+ cells will be followed by an increase in the number of CD8+ cells in COVID-19 patients at Dr. Mohammad Hoesin General Hospital Palembang, Indonesia.